A framework for implementing lean principles in the supply chain management at healthcare organizations: Saudi's perspective - Almutairi, Abdulaziz; Salonitis, Konstantinos; Al-Ashaab, Ahmed (Emerald, 2019)
Purpose The main purpose of this paper is to present lean implementation in hospital supply chain management (HSCM) and propose a new conceptual framework tailored specifically to the needs of Saudi health-care organizations. Design/methodology/approach This paper starts with an in-depth review of existing frameworks or models for lean implementation in health care in general and in HSCM specifically. Based on the literature studies and taking experts’ opinions into account, a new framework for lean implementation in the Saudi HSCM is presented. Findings A new lean implementation framework is offered to decision-makers in the health-care organization for implementing a lean approach in HSCM practices. Research limitations/implications This study focused on health-care organizations, which were selected from hospitals operated by the Ministry of Health and only those hospitals that are accredited by both the Saudi Central Board for Accreditation of Healthcare Institutions and the Joint Commission International. The framework is limited to Saudi health care. Practical implications The lean supply chain management (LSCM) framework is easy to understand and use without much complexity. This simplicity makes the LSCM applicable in health-care settings. Further, LSCM was validated in three different hospitals, and it helped them to identify and improve their non-added activities, thereby readying them for lean deployment in HSCM. Originality/value Little attention has been paid to implementing a lean approach by health-care providers in developing countries. This study presents a new framework that is considered the first of its kind for implementing lean in HSCM in Saudi. This framework could help HSCMs’ decision-makers to implement lean successfully in HSCM practices.
Keywords: Saudi Arabia; health care; framework; lean supply chain management